ANALISIS KALIMAT MAJEMUK BAHASA INDONESIA DALAM TEKS ILMIAH SEBAGAI BAHAN PENGAYAAN MATA KULIAH SINTAKSIS - Hendrik Jehane (Jurnal Lazuardi, 2021)
This research was conducted to realize research-based learning materials. What is meant by research-based learning materials are learning materials developed based on the results of research or scientific studies conducted by the lecturers themselves. Thus, good learning materials are the product of scientific research carried out by the lecturers themselves, not just the compilation of books written by previous experts. The research problems are: (1) What is the structure of compound sentences in scientific texts? (2) What is the relationship between clauses in Indonesian compound sentences in scientific texts? The aims of this study are (1) to explain the structure of compound sentences in scientific texts, (2) to explain the relationship between clauses in Indonesian compound sentences contained in scientific texts. The type of research used is descriptive research. Descriptive research is research that aims to describe a phenomenon as it is at the time of the study. The approach used in this research is a qualitative approach. Qualitative research seeks to reveal the symptoms as a whole and in accordance with the context (holistic-contextual) through collecting data from natural settings by using the researcher himself as a key instrument. The results of the study found that there are three kinds of compound sentences in scientific texts, namely coordinating compound sentences, subordinate compound sentences, and complex compound sentences. Some coordinating compound sentences consist of two clauses and some consist of 3 clauses. Subordinating compound sentences in scientific texts consist of two clauses and some consist of three clauses. Subordinating compound sentence structure consists of five types. Complex compound sentence structure consists of 7 types. There are three kinds of semantic relationships between clauses in Indonesian coordinative compound sentences in scientific texts, namely: (1) resistance relations, (2) selection, and (3) addition/addition. There are four kinds of inter-clause relationships in subordinating compound sentences in scientific texts, namely: (1) objective relationship, (2) conditional relationship, (4) attributive relationship, and causal relationship. There are seven kinds of inter-clause relationships in complex compound sentences, namely: (1) explanatory relationship, (2) concessional relationship, (3) conditional relationship, (4) causal relationship, (5) attributive relationship, (6) effect relationship, and ( 7) relationship goals.